1994
DOI: 10.1093/brain/117.5.1143
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary stepping after chronic spinal cord injury

Abstract: We investigated a pattern of involuntary lower extremity stepping-like movements which recently appeared in a subject with a 17-year history of neurologically incomplete injury to the cervical spinal cord. The movements were rhythmic, alternating and forceful, involved all muscles of the lower extremities and could be reliably evoked by lying the subject down (supine) and extending his hips. Once in this position, the movements continued spontaneously, in the absence of external sensory perturbations, with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(53 citation statements)
references
References 0 publications
1
50
0
2
Order By: Relevance
“…In turn, it has been possible to activate the locomotor CPG by administration i.t., of a variety of pharmacological agents to acutely spinalized marmoset monkeys (Callithrix jacchus) in the absence of phasic afferent input to the spinal cord (Fedirchuk et al, 1998). Spontaneous expression, within weeks or months post-SCI, of rhythmic movements (myoclonus or locomotor-like movements) in humans have also been reported (Pozos and Iaizzo, 1991; Bussel et al, 1992, 1988; Calancie et al, 1994; Chervin et al, 2003; Calancie, 2006; Consentino et al, 2006; Gerasimenko et al, 2008, 2010; Nadeau et al, 2010; Field-Fote et al, 2012; Gorodnichev et al, 2012; Rye and Trotti, 2012). …”
Section: Cpgs In Humans: Evidence From Direct Stimulation and Spontanmentioning
confidence: 94%
See 1 more Smart Citation
“…In turn, it has been possible to activate the locomotor CPG by administration i.t., of a variety of pharmacological agents to acutely spinalized marmoset monkeys (Callithrix jacchus) in the absence of phasic afferent input to the spinal cord (Fedirchuk et al, 1998). Spontaneous expression, within weeks or months post-SCI, of rhythmic movements (myoclonus or locomotor-like movements) in humans have also been reported (Pozos and Iaizzo, 1991; Bussel et al, 1992, 1988; Calancie et al, 1994; Chervin et al, 2003; Calancie, 2006; Consentino et al, 2006; Gerasimenko et al, 2008, 2010; Nadeau et al, 2010; Field-Fote et al, 2012; Gorodnichev et al, 2012; Rye and Trotti, 2012). …”
Section: Cpgs In Humans: Evidence From Direct Stimulation and Spontanmentioning
confidence: 94%
“…No clear answer exists in humans (Calancie et al, 1994; Byrnes et al, 2006). However, related spontaneous plasticity events have clearly been shown in animal models to be associated with some immediate early gene expression (IEG) in CPG-corresponding areas of the spinal cord.…”
Section: Cpgs In Humans: Evidence From Direct Stimulation and Spontanmentioning
confidence: 99%
“…A variety of studies have defined intersegmental neuronal networks in the lumbar spinal cord region that are responsible for simple hindlimb locomotion (5,127,138). These are known as central pattern generators, and evidence suggests that similar generators are found in primate and human spinal cord (28,44,106). Although central pattern generators are under the influence of primary afferents and descending pathways, locomotor activity can be generated without these inputs (105).…”
Section: Intraspinal Transplantsmentioning
confidence: 99%
“…One strategy for achieving this goal is the use of fetal cells, which provide a substrate with both embryonic neurons and neurotrophic factors that may promote axon regeneration or may provide remyelinating substrates that will enhance electrical conduction in the population of spared but demyelinated axons. Schwann cell/peripheral nerve conduits, oligodendrocytes, and, recently, olfactory ensheathing cells have all been used as substrates for promoting remyelination in the spinal cord after SCI (16,28,35,62,75,79,98,109,112,111,139,151,152). More recently, pluripotent stem cells have been proposed as a restorative substrate after SCI (133,136,148).…”
Section: Intraspinal Transplantsmentioning
confidence: 99%
“…For patients with a completely transected spinal cord, it is possible to induce, modulate and stop rhythmic contractions of the trunk and lower limb extensor muscles; however, these rhythmic contractions never occurred spontaneously and had only a one-step cycle duration (Bussel et al 1996). On the other hand, for patients with incomplete lesions, several studies reported subjects with the presence of alternating flexor and extensor activity (Calancie et al 1994). …”
Section: Introductionmentioning
confidence: 99%